The winter pack-ice zone provides a sheltered but food-poor habitat for larval Antarctic krill. Issue 12 (December 2017) - Meyer, Bettina; Freier, Ulrich; Grimm, Volker; Groeneveld, Jürgen; Hunt, Brian; Kerwath, Sven; King, Rob; Klaas, Christine; Pakhomov, Evgeny; Meiners, Klaus; Melbourne-Thomas, Jessica; Murphy, Eugene; et al.
Abstract A dominant Antarctic ecological paradigm suggests that winter sea ice is generally the main feeding ground for krill larvae. Observations from our winter cruise to the southwest Atlantic sector of the Southern Ocean contradict this view and present the first evidence that the pack-ice zone is a food-poor habitat for larval development. In contrast, the more open marginal ice zone provides a more favourable food environment for high larval krill growth rates. We found that complex under-ice habitats are, however, vital for larval krill when water column productivity is limited by light, by providing structures that offer protection from predators and to collect organic material released from the ice. The larvae feed on this sparse ice-associated food during the day. After sunset, they migrate into the water below the ice (upper 20 m) and drift away from the ice areas where they have previously fed. Model analyses indicate that this behaviour increases both food uptake in a patchy food environment and the likelihood of overwinter transport to areas where feeding conditions are more favourable in spring. Winter sea ice is thought to provide critical grazing habitat for overwintering Antarctic krill. In contrast, here the authors show that the pack-ice zone is a food-poor habitat, but does serve as an important sheltering ground for developing larvae.